2015
DOI: 10.1108/jmd-05-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Career success of older workers: the influence of social skills and continuous learning ability

Abstract: Purpose – The purpose of this paper is to examine the influence of the competencies social skills and continuous learning ability on career success and career satisfaction among workers aged 50 or over. Design/methodology/approach – A mixed methods approach consisted of 920 surveys and 11 semi-structured interviews with working individuals aged 50 or above, registered at a job agency specialized in older employees in the Netherlands. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 72 publications
3
39
0
7
Order By: Relevance
“…Perception of career progression changes as employees get older (Bown-Wilson and Parry, 2013;Visagie and Koekemoer, 2014). Hennekam (2015) found that workers have higher career satisfaction as they age. A positive correlation, therefore, exists between age and career satisfaction (Visagie and Koekemoer, 2014).…”
Section: Careermentioning
confidence: 99%
“…Perception of career progression changes as employees get older (Bown-Wilson and Parry, 2013;Visagie and Koekemoer, 2014). Hennekam (2015) found that workers have higher career satisfaction as they age. A positive correlation, therefore, exists between age and career satisfaction (Visagie and Koekemoer, 2014).…”
Section: Careermentioning
confidence: 99%
“…Scholarly works have recently built new models to understand the factors that influence CM and its changeable nature. However, most of these empirical works relied on key organizational factors such as promotion policies and salary structure (Hennekam, 2015). The insufficient understanding of individual factors has been a substantial problem in comprehending the dynamic nature of CM (Haibo, Xiaoyu, Xiaoming, & Zhijin, 2018;Ito & Brotheridge, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…O ageism tem sido estudado a partir da perspectiva da percepção de gestores de RH (BROOKE;TAYLOR, 2005;HASSEL;PERREWE, 1995;HENKENS, 2005;POSTHUMA;6 CAMPION, 2009;ROSCIGNO et al, 2007;WALKER, 1998) ou, ainda, a partir da própria literatura existente sobre o tema (VASCONCELOS, 2015). Autores também se dedicaram a desenvolver um modelo de mudança social sustentável tendo em vista o envelhecimento da força de trabalho (ANGELONI; BORGOLOVI, 2016) e a influência de competências e satisfação com a carreira dos trabalhadores mais velhos (HENNEKAM, 2015). São discutidas também as práticas de gestão da idade que devem ser adotadas nas organizações, a fim de combaterem as barreiras etárias (MALATEST; ASSOCIADOS, 2003;NAEGELE;WALKER, 2006, ARMSTRONG-STASSEN, 2008.…”
Section: Introductionunclassified